Do Management Control Systems Promote Ambidextrous Innovation? The Moderating Role of Leadership Style - Berraies, Sarra; Chaher, Mehrez; Hamdi, Badreddine; Mejri, Tarek (Management international / International Management / Gestiòn Internacional, 2021)
This study develops and tests a model to assess the impact of the ambidextrous management control that refers to a balance between interactive management control system (iMCS) and diagnostic management control (dMCS) on ambidextrous innovation. Our results, based on data collected from 232 senior managers in the context of French companies, indicate that iMCS promotes exploratory innovation, while dMCS has a positive and significant influence on exploitative innovation. Data analysis revealed also that the ambidextrous MCS conducts to ambidextrous innovation. Furthermore, our results show that transformational leadership moderates the relationship between iMCS and exploratory innovation, while transactional leadership moderates the link between dMCS and exploitative innovation. Finally, our findings revealed that ambidextrous leadership reinforces the link between ambidextrous MCS and ambidextrous innovation.